2019
DOI: 10.1158/1078-0432.ccr-18-1189
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Phase I Study of the Selective MET Inhibitor, Savolitinib, in Patients with Advanced Solid Tumors: Safety, Pharmacokinetics, and Antitumor Activity

Abstract: Purpose: Aberrant activation of MET (hepatocyte growth factor receptor) signaling is implicated in the tumorigenesis of human cancers. This phase I study assessed the safety, tolerability, and MTD of the potent and selective MET inhibitor, savolitinib (AZD6094, HMPL-504, volitinib). Patients and Methods: This open-label, multicenter doseescalation and-expansion study evaluated oral savolitinib for patients with locally advanced or metastatic solid tumors. A 3 þ 3 design assessed repeated daily (QD) and twice d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 26 publications
7
56
0
Order By: Relevance
“…Indeed, there is clinical rationale for exploring ALK/MET combinations besides lorlatinib/crizotinib. For example, while cross-trial comparisons suggest that most adverse events, including nausea/vomiting and edema, occur at comparable rates with the three MET TKIs evaluated in cell lines (crizotinib, capmatinib, savolitinib), 4,27,28 the blood-brain barrier penetration of capmatinib is superior to crizotinib. Capmatinib may therefore be a more optimal partner for lorlatinib in patients with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is clinical rationale for exploring ALK/MET combinations besides lorlatinib/crizotinib. For example, while cross-trial comparisons suggest that most adverse events, including nausea/vomiting and edema, occur at comparable rates with the three MET TKIs evaluated in cell lines (crizotinib, capmatinib, savolitinib), 4,27,28 the blood-brain barrier penetration of capmatinib is superior to crizotinib. Capmatinib may therefore be a more optimal partner for lorlatinib in patients with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…AMG 337, an oral ATP-competitive TKI specific to MET, caused a strong response in patients with MET-amplified upper gastrointestinal tract cancer in phase I and II trials. 325,326 Savolitinib, a selective MET inhibitor, displayed marked antitumour potential under experimental conditions and appeared to be effective against renal cell cancer 327,328 and is being investigated in a metastatic CRC phase I trial. Capmatinib, another selective MET inhibitor, has been demonstrated as a good supplementary agent to gefitinib in patients with EGFR-mutant, MET-amplified NSCLC.…”
Section: The Hgf/c-met Pathwaymentioning
confidence: 99%
“…The most common AEs were increased blood creatinine (52%), nausea (48), decreased appetite (41%), vomiting (39%), and diarrhea (25%). The gastrointestinal symptoms, such as vomiting and diarrhea, were also observed frequently with savolitinib [17], while less reported (≤ 10%) with BIP-9016M. Furthermore, the ATTENTION trial was terminated because of an increased incidence of interstitial lung disease in the tivantinib group [30].…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies that directly against HGF or MET, such as onartuzumab, rilotumumab, and emibetuzumab, have entered early phase clinical trials and demonstrated promising activity [13,14]. Several small-molecule tyrosine kinase inhibitors that inhibit a number of intracellular pathways including MET, such as cabozantinib, savolitinib, and capmatinib, are also under development [15][16][17].…”
mentioning
confidence: 99%